Assessing the Effectiveness of Budget Allocation in Health Human Resource Planning - Rachman, Abdul Nasir; Pahlawansah, Haniwijaya; Aprilius, Adrianus (Journal of Entrepreneur, Business and Management, 2025)
This study aims to examine the effectiveness of budget utilization in the planning of health workforce requirements at Intan Jaya District Hospital, Central Papua Province. The research applies a qualitative method with a descriptive approach. Data were obtained through field observations, in-depth interviews with five key informants, and a review of relevant documents. The findings reveal that the effectiveness of budget utilization in fulfilling the demand for health personnel at Intan Jaya District Hospital is still confronted with several challenges. These challenges include limited budget allocation, discrepancies between planned and realized budgets, and an imbalance between the existing number of health workers and the actual workforce needs. Several factors were identified as supporting the effective use of budgets, including proper budget planning, strong managerial support, active participation of health personnel in planning processes, transparency and accountability in financial management, flexibility in budget allocation, and continuous monitoring and evaluation. The study also shows that budget utilization has contributed to an increase in the number of health workers; however, disparities in welfare and incentive distribution remain due to less optimal budget allocation. Therefore, more adaptive and responsive policies in budget planning and management are required to ensure the availability of sufficient health personnel and to improve the quality of health services for the community in Intan Jaya Regency.Keywords: Effectiveness, Budget, Health Workers, Regional Public Hospital, Central Papua.